2015
DOI: 10.1080/10454446.2014.949990
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Preferences and Attitudes Toward Local Food Products

Abstract: In recent years, consumers’ interest in local food has significantly\ud increased. Several studies in the agricultural economics andmarketing\ud literature have analyzed mainly consumers’ preferences for local food\ud products. In this study, we perform a consumer segmentation with\ud regard to consumer behavior toward local food. We collected data\ud from a survey conducted during summer 2010 in Naples, South Italy.\ud Consumer segments were identified taking account of five aspects: (1)\ud food consumption s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
122
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(144 citation statements)
references
References 39 publications
17
122
1
4
Order By: Relevance
“…Evidence from the literature suggests that the group of factors related to interaction with the destination and food products, which can influence food consumption in the context of tourism, comprises travel behaviour, knowledge of local food products, and evaluation of local food products (Aprile et al, 2012(Aprile et al, , 2016Dimara & Skuras, 2003;Frisvoll et al, 2016;Getz, 2000;Ryu & Jang, 2006;Sims, 2009;Skuras et al, 2006;Tse & Crotts, 2005).…”
Section: Interaction With the Destination And Food Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from the literature suggests that the group of factors related to interaction with the destination and food products, which can influence food consumption in the context of tourism, comprises travel behaviour, knowledge of local food products, and evaluation of local food products (Aprile et al, 2012(Aprile et al, , 2016Dimara & Skuras, 2003;Frisvoll et al, 2016;Getz, 2000;Ryu & Jang, 2006;Sims, 2009;Skuras et al, 2006;Tse & Crotts, 2005).…”
Section: Interaction With the Destination And Food Productsmentioning
confidence: 99%
“…More people have been exposed to foreign food products due to the influence of globalization, even before they begin an overseas trip, which means they have already had the opportunity to become familiar with a diversity of foreign foods ( Kim et al (2009Kim et al ( , 2013, Kim and Eves (2012) Food-related personality traits Food neophilia Mak (2011), Cohen andAvieli (2004), Fischler (1988), Kim et al (2009Kim et al ( , 2013, Mak, Lumbers, Eves, and Chang (2012) (1998), Youn and Kim (2017) Finally, the interest demonstrated in relation to local food products could be based on a set of attributes that range from a concern for environmental and social sustainability through demands for food products that are safe, distinctive, and traceable (Boniface, 2003;Mynttinen et al, 2015;Zagata, 2012). The qualities associated with local products include being fresh, tasty, nutritious and healthy, and safe (Aprile et al, 2016). All these aspects could drive consumers' evaluation of local food products and encourage them to pay a price premium in this regard (Aprile et al, 2012;Caputo et al, 2013;Carpio & Isengildina-Massa, 2009;Schneider & Francis, 2005).…”
Section: Interaction With the Destination And Food Productsmentioning
confidence: 99%
“…The results of a number of studies about brand image and region of origin have emphasised stronger relationships between consumers' purchasing intentions, consumption frequencies and extrinsic quality attributes at the point of sale (Enneking et al, 2007;Kokthi et al, 2014;Uzundumlu and Topcu, 2016;Weber et al, 2015;Bartsch et al, 2016). The same findings are true for studies regarding actual and visual qualities (Koutroulou and Tsourgiannis, 2011;Boniface et al, 2013;Cacciolatti et al, 2015;Topcu, 2015;Aprile et al, 2016;Pinto et al, 2016). These findings are also compatible with the results of this study, which shows that extrinsic dairy product attributes are crucial in the purchase decision-making process for medium and light users.…”
Section: Results Of Multiple Regression and Correlation (Mrc) Analysesmentioning
confidence: 89%
“…A number of studies on consumer purchasing decisions have shown that local dairy products with PDO and PGI branding are commonly equated with higher positive purchase motivation and willingness to pay due to their intrinsic quality attributes, being more natural, fresh, healthy and safe than conventional dairy products. Consumers, therefore, have been shown to pay particular attention to food safety in the decision to buy dairy products (generally local cheese varieties) in studies conducted by Bellows et al (2010), Lalor et al (2011), Tsourgiannis et al (2011), Topcu and Uzundumlu (2012), Boniface et al (2013), Topcu (2015), Aprile et al (2016), Giampietri et al (2016), Hsu et al (2016) and Zhao et al (2016).…”
Section: Results Of Multiple Regression and Correlation (Mrc) Analysesmentioning
confidence: 99%
“…Indeed, the consumer has increasingly used the criterion of personal trust to a specific certification. For example, in Italy, the quality features of a product are often connected to local productions or local foodstuffs (Aprile et al, 2016). Local food is perceived as characterized by a large variety of benefits, that range from the satisfaction of enjoying a homemade authentic food product, to the local-food intrinsic ability to enhance the sustainability of the food system, reducing the carbon footprint and providing new market opportunities for local farms (Guerrero et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%